Aggression in International Law: The Crime of a State and Criminal Responsibility of an Individual - Enis Omerović (Društvene i Humanističke Studije, 2022)
The paper covers unlawful use of force in international law by states to explore the general concept and definition of aggression in the law of state responsibility and for criminal responsibility of individuals. The genesis of the concept of aggression in the XX century is analyzed. The paper describes problems that arose in defining the aggression that accompanied the efforts to ban any threat of force and the use of force by international law provisions, which was over with adopting the United Nations Charter in 1945. The responsibility of a State for the internationally wrongful act in question was accompanied by the criminal responsibility of individuals for the same international crime. The analysis of cases before the International Court of Justice in The Hague, and the analysis of the work of the United Nations Security Council, reveal their practice in terms of which of the above authorities has priority in finding State responsibility? Equally, we seek to identify the weaknesses concerning the definition of aggression adopted as an expression of political compromise in Annex to the 1974 UN General Assembly Resolution, and whether the 2010 Kampala definition contained in the amendments to the Rome Statute may be considered inadequate in trying of the International Criminal Court to fight impunity and to participate in the prevention of future crimes of aggression through its work and actions. Ultimately, is the aggression any threat or violation of international peace and security by the state? If aggression is a true-crime of a State, does that mean that only the highest officials of the state will be criminally responsible for the crime in question?